pH responsive N-succinyl chitosan/Poly (acrylamide-co-acrylic acid) hydrogels and in vitro release of 5-fluorouracil - Bashir, S.; Teo, Y.Y.; Naeem, S.; Ramesh, S.; Ramesh, K. (Public Library of Science, 2017)
There has been significant progress in the last few decades in addressing the biomedical applications of polymer hydrogels. Particularly, stimuli responsive hydrogels have been inspected as elegant drug delivery systems capable to deliver at the appropriate site of action within the specific time. The present work describes the synthesis of pH responsive semi-interpenetrating network (semi-IPN) hydrogels of N-succinyl-chitosan (NSC) via Schiff base mechanism using glutaraldehyde as a crosslinking agent and Poly (acrylamide-coacrylic acid)(Poly (AAm-co-AA)) was embedded within the N-succinyl chitosan network. The physico-chemical interactions were characterized by Fourier transform infrared (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and field emission scanning electron microscope (FESEM). The synthesized hydrogels constitute porous structure. The swelling ability was analyzed in physiological mediums of pH 7.4 and pH 1.2 at 37°C. Swelling properties of formulations with various amounts of NSC/Poly (AAm-co-AA) and crosslinking agent at pH 7.4 and pH 1.2 were investigated. Hydrogels showed higher swelling ratios at pH 7.4 while lower at pH 1.2. Swelling kinetics and diffusion parameters were also determined. Drug loading, encapsulation efficiency, and in vitro release of 5-fluorouracil (5- FU) from the synthesized hydrogels were observed. In vitro release profile revealed the significant influence of pH, amount of NSC, Poly (AAm-co-AA), and crosslinking agent on the release of 5-FU. Accordingly, rapid and large release of drug was observed at pH 7.4 than at pH 1.2. The maximum encapsulation efficiency and release of 5-FU from SP2 were found to be 72.45% and 85.99%, respectively. Kinetics of drug release suggested controlled release mechanism of 5-FU is according to trend of non-Fickian. From the above results, it can be concluded that the synthesized hydrogels have capability to adapt their potential exploitation as targeted oral drug delivery carriers.